Nilai-Nilai Dakwah Pagelaran Wayang Kulit Kanjeng Pangeran Oleh Raden Mas Aflakha Mangkunegara di Desa Lajo Lor Kecamatan Singgahan Kabupaten Tuban - Muthowah, Aflachal; Rif’ah Ainiyah (Jurnal Multidisiplin Indonesia, 2023)
This research aims to find out how da'wah activities attract more attention so that the da'wah message conveyed can be well received. Da'wah Raden Mas Aflakha Mangkunegara uses shadow puppets as a medium for preaching activities through the Kanjeng Pangeran Organization, shadow puppet performances are one of the effective media for conveying da'wah messages. The approach used in this research is descriptive qualitative. Data collection techniques in this research are observation, interviews and documentation. The data analysis technique used is the Miles and Huberman model analysis, namely data reduction, data display, and conclusion drawing/verification. Data validity uses reliability, transferability, dependability and confirmability. Credibly researched using persistent observation. The results of research on the da'wah values contained in the wayang kulit performance presented by Kanjeng Pangeran contain elements of social values, namely Aqidah and moral values, and religious values that combine Javanese traditions with Islamic nuances. The strategy used by Raden Mas Aflakha Mangkunegara in the Kanjeng Pangeran wayang kulit performance in preaching is to take advantage of the conditions of the surrounding community, where the people are thirsty for entertainment and the dominant abangan community is still steeped in Javanese culture.